Ventricular unloading causes prolongation of the QT interval and induces ventricular arrhythmias in rat hearts - Schwoerer, Alexander Peter; Biermann, Daniel; Ehmke, Heimo (Frontiers in Physiology, 2024)
Introduction: Ventricular unloading during prolonged bed rest, mechanical circulatory support or microgravity has repeatedly been linked to potentially life-threatening arrhythmias. It is unresolved, whether this arrhythmic phenotype is caused by the reduction in cardiac workload or rather by underlying diseases or external stimuli. We hypothesized that the reduction in cardiac workload alone is sufficient to impair ventricular repolarization and to induce arrhythmias in hearts. Methods: Rat hearts were unloaded using the heterotopic heart transplantation. The ECG of unloaded and of control hearts were telemetrically recorded over 56 days resulting in >5x10 6 cardiac cycles in each heart. Long-term electrical remodeling was analyzed using a novel semiautomatic arrhythmia detection algorithm. Results: 56 days of unloading reduced left ventricular weight by approximately 50%. While unloading did not affect average HRs, it markedly prolonged the QT interval by approximately 66% and induced a median 10-fold increase in the incidence of ventricular arrhythmias in comparison to control hearts. Conclusion: The current study provides direct evidence that the previously reported hypertrophic phenotype of repolarization during cardiac unloading translates into an impaired ventricular repolarization and ventricular arrhythmias in vivo. This supports the concept that the reduction in cardiac workload is a causal driver of the development of arrhythmias during ventricular unloading.